A novel mutation in the tropomyosin 1 gene in a Chinese patient with hypertrophic cardiomyopathy. Issue 1 (31st December 2022) - Gong, Ke; Wu, Qin; Xie, Ting; Luo, Yong; Guo, Hui; Tan, Zhiping; Chen, Jinlan; Yang, Yifeng; Xie, Li
Abstract : Hypertrophic cardiomyopathy (HCM) is an inherited heart disease characterized by left ventricular hypertrophy. Although sarcomeric gene mutations can explain many HCM cases, the genetic basis of approximately half of HCM cases remains elusive. Here, we report the case of a 30-year-old woman with HCM after imaging and pathological examinations. We identified a novel mutation in a pathogenic gene from the HCM patient through whole-exome sequencing. A heterozygous missense mutation in exon 1 of the α-tropomyosin ( TPM1 ) gene (NM_000366.5:exon1:c.71A > G) was found based on patient sequencing data. The mutation resulted in glutamine replacing arginine (p.Gln24Arg). This mutation was expected to cause significant and deleterious changes in the structure of the TPM1 protein. Therefore, according to pathogenicity assessment guidelines, the mutation was considered likely pathogenic. We found that most of these mutations are related to cardiomyopathy and majority of them are in exon 1 and are missense mutations. TPM1 mutations are thus a common cause of HCM and other congenital heart defects. Thus, a novel missense variant, p.Gln24Arg, in the TPM1 gene is associated with the autosomal dominant disease HCM. These results expand the knowledge spectrum of TPM1 gene function.